Differentiation of Laboratory-Obtained Ixodes ricinus × Ixodes persulcatus Hybrid Ticks: Selection of Suitable Genes - Alexander G. Litov; Oxana A. Belova; Sergey V. Bugmyrin; Ivan S. Kholodilov; Lidia Iu. Romanova; Galina G. Karganova (Microorganisms, 2022)
Ixodes ricinus and Ixodes persulcatus ticks are the main vectors of tick-borne encephalitis virus and some bacterial pathogens. The regions where these tick species live overlap, forming large sympatric areas. It has previously been shown that these tick species have no morphological barrier, and interspecies crossing is possible with the appearance of sterile hybrids. It has also been shown that hybrid larvae and nymphs can be differentiated using discriminant functions based on a set of morphological features. However, such an approach is laborious and rather ineffective with adult ticks, making a molecular approach necessary. In the current work, we tested the ability of different systems to differentiate laboratory-obtained hybrid ticks. Our data suggest that commonly used primer sets that target rRNA are unsuitable for hybrid tick determination, likely due to the rRNA region being linked with the X chromosome in I. ricinus and I. persulcatus ticks. We tested several primer sets targeting different non rRNA genes to assess their ability to determine hybrids. The best primer set, Toll_R, targeting the putative Toll gene, showed little to no bias when used for DNA amplification from hybrid ticks. Thus, Toll gene can be further used for hybrid detection.